Managing construction and infrastructure in the 21st century Bureau of Reclamation (National Academies Press, 2006)
In the more than 100 years since its formation, the U.S. Bureau of Reclamation of the Department of Interior (DOI), through its construction program, has brought water, electric power, and recreation facilities to millions of people in the Western United States. With major water and power systems in place, the Bureau's attention has now turned to operation, maintenance, repair, and modernization of those facilities in an environmentally and economically sound manner. To help with this effort, DOI asked the NRC to advise the Bureau on appropriate organizational, management, and resource configurations to meet its construction, maintenance, and infrastructure requirements for its missions of the 21st century. This report presents an assessment of the requirements facing the Bureau in the 21st century, an analysis of good practices and techniques for addressing those challenges, and a review of workforce and human resource needs. The report also provides alternative scenarios that describe possible future organizations for infrastructure management.